Physical activity, life satisfaction and adjustment to illness in women after treatment of breast cancer - Malicka, Iwona; Szczepańska-Gieracha, Joanna; Jankowska, Ewelina; Woźniewski, Marek; Rymaszewska, Joanna (Contemporary Oncology/Współczesna Onkologia, 2011)
Aim of the study: To evaluate the impact of different types of physical activity on life satisfaction, acceptance of illness and adaptation to breast cancer among women after treatment. Material and methods : 36 women after treatment of breast cancer with mean age of 59 years (±10.2) were assessed with the satisfaction of life scale, acceptance of illness scale, and Mental Adjustment to Cancer Scale. Physical activity within the group was evaluated. Results : Those women (81% of the group) who participated in Breast Cancer Survivors’ Club meetings had higher scores on the AIS (p = 0.01), which means better acceptance of illness and disability. They also had high awareness of the importance of physical activity for recovery after treatment of breast cancer. 94% of the group confirmed that regular physical training was necessary. 82% of them found that they spent more time on training than before the operation. Within the most active subgroup (more than 5 types of activity) higher scores of the fighting spirit item in the Mini-MAC scale (p = 0.019) were observed. Tourist trips (fighting spirit p < 0.01, positive attitude: p = 0.055, constructive style: p < 0.01) and dance (SWLS: p < 0.05, AIS: p < 0.05) had a significant impact on quality of life. Conclusions : Women after treatment of breast cancer had high awareness of the impact of physical activity on recovery. The study subgroup of women who were most active had a better strategy of fighting spirit. Among many types of physical activity, tourist trips and dance were the most important for quality of life. Physical activity seemed to be profitable also for the subgroup outside the Breast Cancer Survivors’ Club.